Two Dreams : - Lim, Shirley. (Feminist Press, 1997)
The stories of Shirley Geok-lin Lim reflect the complex mosaic of her world. As their setting shifts from the tradition-bound terrain of Malaysia to the liberating but confusing territory of the United States, Lim's stories capture the poignant and perplexing experience of immigrant women, who, torn between two cultures, must build their own values and homelands from within. Two Dreams draws together the best of Lim's short fiction from nearly three decades, most of it never before available in the United States.